Effect of Education Level and Work Experience on Performance of Rantauprapat Hospital Employees - Maulida Simamora; Marlina Siregar; Nurintan Asyiah Siregar (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to determine the effect of level of education and work experience on the performance of employees of RSUD Rantauprapat . This type of research is associative research. The population used in this study were employees of the Rantauprapat Hospital. Data collection techniques were carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study used SPSS. The results of this study indicate that for the education level variable (X1), the t - count value (2.921) > t table 1 , 664) and the significance level of 0.00 0 <0.05. This means that partially the level of education affects the performance of employees at RSID Rantauprapat . For work experience variable (X2), obtained t count (3.921) > t table (1, 661) and a significance level of 0.00 0 < 0.05. This means that partially work experience has an effect on employee performance